Poly(2-oxazoline) macromonomers as building blocks for functional and biocompatible polymer architectures. (December 2019) - Pizzi, David; Humphries, James; Morrow, Joshua P.; Fletcher, Nicholas L.; Bell, Craig A.; Thurecht, Kristofer J.; Kempe, Kristian
Graphical abstract: Abstract: Poly(2-oxazoline)s (POx) have received significant attention as next-generation biomaterials due to their promising biomedical and physicochemical properties. In recent years, the combination of POx with other polymer classes has further expanded their breadth of applications. The most promising and studied approach is the utilisation of POx based macromonomers, which are easily accessible because of the modularity of the cationic ring-opening polymerisation. These tuneable macromonomers are available for secondary polymerisations, which has allowed incorporation of POx in diverse architectures. This review article aims to highlight the abundance of reported methods for POx macromonomer synthesis and to discuss the research performed using these building blocks for the design of sophisticated functional architectures.